Positive politeness strategies during online learning: A cyberpragmatic study - Hari Kusmanto; Pratomo Widodo (Universitas Syiah Kuala, 2022)
Language politeness and character education are crucial in the era of education disruption, particularly in terms of learning communication. Problems with language politeness happen when communication is mediated by electronic media, such as WhatsApp in particular, because it allows undergraduates to be more open in conveying their intentions, including to the lecturers regarding the learning goals. This study aims to describe the forms of language politeness during online learning in higher education. The study used a descriptive qualitative approach. The data of this study were utterances consisting of language politeness, and the data sources were undergraduates’ utterances to their lecturer. The data collection techniques were documenting, reading, and note-taking. The data were analyzed through referential identity, extra lingual interactive model, and politeness strategies proposed by Brown and Levinson (1987) and Maricic (2000). Cyberpragmatic perspective perceives the positive politeness strategies with the help of external context, in this case, the virtual learning context, to find out whether there were positive politeness strategies in the utterances. The findings indicate that positive politeness strategies during online learning using cyberpragmatic approach are represented in six forms: paying attention, using identity markers, looking for agreement, avoiding conflict, creating humor, and showing an optimistic attitude. This study recommends that positive politeness strategies can be used as a pillar of developing and strengthening character education in learning, especially in universities.